Baseband Feedback for Frequency-Domain-Multiplexed Readout of TES X-ray Detectors - Den Hartog, Roland; Boersma, D; Bruijn, M; Dirks, B; Gottardi, L; Hoevers, H; Hou, R; Kiviranta, M; De Korte, P; Van Der Kuur, J; Van Leeuwen, B J; Nieuwenhuizen, A; et al. (Proceedings of the 13th International Workshop, 2009)
The linear dynamic range available for Frequency-Domain-Multiplexed (FDM) read-out of TES X-ray detectors is seriously limited by the SQUID current amplifiers used for the read-out of TES-detectors. Baseband feedback is one of the ways to increase the linearity and dynamic range of SQUIDs for the TES signals. Baseband feedback is realized by demodulation, and low-pass filtering of the AM-signals at the amplified summing point, thereby retrieving the signals for each detector, and subsequent remodulation and summing of the individual detector signals with phase compensation for the delay and phase rotation at each carrier frequency. This algorithm creates sufficient gain-bandwidth at and around each carrier frequency (1-10 MHz) to reduce the error signal at the input of the SQUID amplifier for both the AC-carriers and the signals modulated onto them. The paper presents the principle, modeling, and initial results.